(untitled) (Colombia Medica, 1987)
The crisis phenomena induced in vitro using sera of 80 patients from a malarious area of the Colombian Pacific Coast is described. Specific anti-P. falciparum blood forms antibodies were determined by an immunofluorescence assay, and the intraerythrocytic development of the parasite was quantified by incorporating Tritium labeled hypoxanthine. The crisis phenomenon was independent of the antimalarial antibodies and did not correlate with the parasitemin¡a of the patients.